A Quantitative Study of Water Pollution of Rural Area in Gaya District (Journal of Advances and Scholarly Researches in Allied Education, 2024)
A study deals with “A Quantitative Study of Water Pollution of Rural Area in Gaya District.” A method was to studded that on empirical in nature. documentary, historical, analytical and descriptive methods have been used. The information has been collected on rural areas in Gaya district and sample was taken 50 (N) primary data while, secondary data has been collected from water pollution related areas etc. To study the efficacy of constitutional and statutory provisions in preventing and controlling water pollution. Hypothesis was that Growing population, industrialization and excessive use of pesticides are the main causes of water pollution, The results was to found that awerensess of level of water and causes of water pollution.